Parental involvement in Finnish day care – what do early childhood educators say? - Sevcan Hakyemez-Paul; Päivi Pihlaja; Heikki Silvennoinen (EECERA, Routledge - Taylor & Francis Group, 2022)
Research conducted in recent decades shows that parental involvement (PI) plays a significant role in the academic achievement and the healthy development of children. Gaining a better understanding of early childhood educators’ views and the reasons for insufficient practices is important for improving PI. This mixed-method research investigates the views on PI held by early childhood educators in Finland. A representative sample of 287 educators from Helsinki completed a questionnaire which provided quantitative data and qualitative material. The results show that Finnish early childhood educators have positive attitudes towards PI and its various types in general. Learning at home is the most popular type of PI. The participants state that difficulties in PI are often caused by poor parental motivation and a lack of time on the part of both educators and parents.